Efisiensi Turbin Kincir Air Akrilik Undershot 8 Sudu 15o - Tampubolon, Rizky; Hermawan, Indra; Idris, Muhammad (Jurnal Ilmiah Teknik Mesin & Industri (JITMI), 2023)
Electricity is one of the vital energy sources that is highly demanded by society. However, there is still an imbalance in the availability of electricity in Indonesia, especially in remote or isolated areas that are difficult to reach by the national power grid (PLN). To address this issue, one of the solutions that can be employed is Micro Hydro Power Plant (PLTMH), which is a renewable power generation system. In PLTMH, water turbines are utilized as a medium to generate rotation through the force exerted by the flowing water from a certain height. The water head plays a significant role in the performance of the water turbine, where a higher waterfall and impact on the turbine blades result in faster rotation and greater energy production. This study presents the experimental results of an Undershot Water Turbine made of Acrylic material with 8 blades and a blade angle of 15°. The experiment employed a water volume of 58 liters and a water gate opening of 3 cm. The results showed that the water turbine generated a power of 0.41584 watts, while the power produced by the flowing water was 1.23186 watts. The efficiency of the water turbine in this experiment reached 33%. Based on this research, it can be concluded that the proper utilization of an Undershot Water Turbine made of Acrylic material with an appropriate number and angle of blades can yield significant power output. Moreover, the achieved efficiency level of 33% demonstrates that the water turbine can serve as an efficient alternative for renewable electricity generation.